First report of novel genetic array aacA4-blaIMP-25-oxa30-catB3 and identification of novel metallo-β-lactamase gene blaIMP25: A Retrospective Study of antibiotic resistance surveillance on Psuedomonas aeruginosa in Guangzhou of South China, 2003–2007. (June 2016) - Yu, Guangchao; Wen, Wangrong; Peters, Brian M.; Liu, Junyan; Ye, Congxiu; Che, Yuchuan; Liu, Juzhen; Cao, Kaiyuan; Xu, Zhenbo; Shirtliff, Mark E.
Abstract: Carbapenem, imipenem and meropenem have been broadly prescribed contributing to the global occurrence and prevalence of carbapenem resistance in Psuedomonas aeruginosa, and the associated resistance genotypes remains clinically significant. A retrospective surveillance had been conducted on 499 P. aeruginosa isolates in South China during 2003–2007, including antimicrobial resistance and characterization of MBLs on carbapenem-resistant strains. One hundred and sixty-four out of 499 strains were carbapenem-resistant, with 11, 4 and 5 strains positive for bla IMP-9, bla IMP-25 and bla VIM-2, respectively. Sixteen out of 20 isolates were positive for intI1 and contained identical flanking regions (as indicated inKM384735 ), and all tested isolates containing the qacE△1 - sul1 of the typical 3′-conserved region. A novel bla IMP-25 metallo-β-lactamase and a genetic array of aacA4 - bla IMP-25 - oxa30 - catB3 have been discovered from this retrospective surveillance on antimicrobial resistance of P. aeruginosa . Highlights: A Retrospective Study on Psuedomonas in South China during 2003–2007 was conducted. Multi-resistance was found in 14.2% of the tested isolates. Positive MBL production was confirmed in 13.4% (22/164) of carbapenem-resistant strains. Four out of 166 carbapenem-resistant strains carried bla IMP-25 . This is the first report of aacA4 - bla IMP-25 - oxa30 - catB3 from class 1 integron.